Die Unterschenkelfraktur als Sporttrauma - Klinischer Outcome und Sportfähigkeit nach operativer Versorgung - Konrad, G.; Markmiller, M.; Rüter, A. (Sportverletzung Sportschaden, 2002)
Sports-related tibial diaphyseal fractures occur mainly in contact sports and in downhill skiing. Due to the demand for rapid healing and the need for an early recovery of the mostly young patients, surgery is almost imperative. The clinical outcome and sports ability of 38 patients with sports-related tibial diaphyseal fractures were investigated 29 months after the initial trauma. Soccer and wintersport accounted for the majority of injuries. Operative treatment has been mainly unreamed nailing. After an average of 10.3 months 32 patients (84 %) returned to sports. Almost one-third, however did change over to a less stressful sport. 6 patients discontinued their sports activity. The activity score of Tegner and Lysholm declined from 5.4 before the injury to 3.4 six months after surgery. At the time of the follow-up examination this rose to 4.6. The long-term result scored after Merchant and Dietz showed 87 % excellent and good results. For the majority of sports-related tibial diaphyseal fractures, unreamed nailing is the treatment of choice.